Integration of Cell-Free Expression and Solid-State NMR to Investigate the Dynamic Properties of Different Sites of the Growth Hormone Secretagogue Receptor - Pacull, Emelyne M.; Sendker, Franziska; Bernhard, Frank; Scheidt, Holger A.; Schmidt, Peter; Huster, Daniel; Krug, Ulrike (Frontiers in Pharmacology, 2020)
Cell-free expression represents an attractive method to produce large quantities of selectively labeled protein for NMR applications. Here, cell-free expression was used to label specific regions of the growth hormone secretagogue receptor (GHSR) with NMR-active isotopes. The GHSR is a member of the class A family of G protein-coupled receptors. A cell-free expression system was established to produce the GHSR in the precipitated form. The solubilized receptor was refolded in vitro and reconstituted into DMPC lipid membranes. Methionines, arginines, and histidines were chosen for 13C-labeling as they are representative for the transmembrane domains, the loops and flanking regions of the transmembrane α-helices, and the C-terminus of the receptor, respectively. The dynamics of the isotopically labeled residues was characterized by solid-state NMR measuring motionally averaged 1H-13C dipolar couplings, which were converted into molecular order parameters. Separated local field DIPSHIFT experiments under magic-angle spinning conditions using either varying cross polarization contact times or direct excitation provided order parameters for these residues showing that the C-terminus was the segment with the highest motional amplitude. The loop regions and helix ends as well as the transmembrane regions of the GHSR represent relatively rigid segments in the overall very flexible receptor molecule. Although no site resolution could be achieved in the experiments, the previously reported highly dynamic character of the receptor concluded from uniformly 13C labeled receptor samples could be further specified by this segmental labeling approach, leading to a more diversified understanding of the receptor dynamics under equilibrium conditions.